The concept and meaning of work among physically disabled workers in service industry - Go, Jose (1999)
The study describes the concept and meaning of work from the perspective of three physically disabled workers (1 blind, 1 deaf/mute, 1 paraplegic) using a qualitative phenomenological research methodology. Results of the case studies reveal that the concept of work by the participants is generally economic-related, i.e., revolving around income and provision of materials. Participants expressed the concept of work in local terms-- pangita ("to see" or " to find") and pangabuhi ("life" or "to live"). When these two terms are combined to form gapangita sang pangabuhian, the concept of work acquires a deeper meaning as "working for life".
Keywords: Persons with disabilities; Physically disabled workers